A review on plasma-catalytic methanation of carbon dioxide – Looking for an efficient catalyst. (December 2019) - Dębek, Radosław; Azzolina-Jury, Federico; Travert, Arnaud; Maugé, Françoise
Abstract: The review focuses on presenting recent findings on CO2 methanation plasma-catalytic process. In order to understand the background of the research, firstly a summary of thermal catalytic CO2 methanation is presented. Secondly, discussion on plasma CO2 hydrogenation including various plasma types and process parameters is addressed. Catalytic CO2 methanation is already an industrial process achieving high conversions of CO2 and CH4 yield. However, the need to optimize this process (decrease reaction temperature, increase catalyst activity, selectivity and stability) resulted in the development of plasma technology. It was proven that plasma can actively convert CO2 . The main product of plasma CO2 hydrogenation is, however, carbon monoxide. Therefore, a plasma process is not selective for CH4 production and the presence of a catalyst is necessary to effectively convert CO2 to CH4 under plasma conditions. The study of plasma-catalytic CO2 methanation is quite a new topic focused mainly on the application of dielectric barrier discharge plasma and Ni-based catalyst. This review summarizes recent advantages of the plasma catalytic process and discusses possible directions of catalyst development. Graphical abstract: Image 1 Highlights: Plasma-catalytic CO2 methanation may become an important technology for H2 storage and CO2 valorisation. CO2 activation in plasma requires catalyst to produce CH4 . Catalyst for plasma process should be active in thermal catalysis. Beneficial effect of plasma-catalysis may be enhanced via adjustment of catalyst properties and plasma operating conditions.